Evaluation and Assessment in Software Engineering 2021
DOI: 10.1145/3463274.3463333
|View full text |Cite
|
Sign up to set email alerts
|

Self-Claimed Assumptions in Deep Learning Frameworks: An Exploratory Study

Abstract: Deep learning (DL) frameworks have been extensively designed, implemented, and used in software projects across many domains. However, due to the lack of knowledge or information, time pressure, complex context, etc., various uncertainties emerge during the development, leading to assumptions made in DL frameworks. Though not all the assumptions are negative to the frameworks, being unaware of certain assumptions can result in critical problems (e.g., system vulnerability and failures, inconsistencies, and inc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…They conducted a descriptive study with 122 master students, and the students identified and extracted 845 assumptions from the models created by the students. Yang et al conducted an exploratory study of assumptions made in the development of nine popular deep learning frameworks (e.g., TensorFlow, Keras, and PyTorch) on GitHub [11]. They identified and extracted 3,084 assumptions from the code comments in over 50,000 files of the deep learning frameworks.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…They conducted a descriptive study with 122 master students, and the students identified and extracted 845 assumptions from the models created by the students. Yang et al conducted an exploratory study of assumptions made in the development of nine popular deep learning frameworks (e.g., TensorFlow, Keras, and PyTorch) on GitHub [11]. They identified and extracted 3,084 assumptions from the code comments in over 50,000 files of the deep learning frameworks.…”
Section: Related Workmentioning
confidence: 99%
“…The count of the identified SCAs could be larger than the search results (e.g., count of messages in the commits of the Keras repository), since each issue, PR, or commit may include multiple SCAs. For example, an issue 11 of Keras mentions: "Assume we are trying to learn a sequence to sequence map. For this we can use Recurrent and TimeDistributedDense layers.…”
Section: B Evaluation Of Sca Identificationmentioning
confidence: 99%
See 2 more Smart Citations